2018
DOI: 10.1158/0008-5472.can-17-2933
|View full text |Cite|
|
Sign up to set email alerts
|

Truncated Glioma-Associated Oncogene Homolog 1 (tGLI1) Mediates Mesenchymal Glioblastoma via Transcriptional Activation of CD44

Abstract: The molecular pathways driving mesenchymal glioblastoma (GBM) are still not well understood. We report here that truncated glioma-associated oncogene homolog 1 (tGLI1) is a tumor-specific transcription factor that facilitates GBM growth, is enriched in the mesenchymal subtype of GBM and glioma stem cells (GSC), and promotes mesenchymal GSC by upregulating transcription of CD44. In an orthotopic GBM xenograft mouse model, tGLI1-overexpressing tumors grew more aggressively with increased proliferation and angiog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 43 publications
1
40
0
Order By: Relevance
“…In HuH7 and mNeat1v1-overexpressing HepG2 cells, the expression of CD44s was observed, while other splicing variants were not detected. It has been reported that CD44 expression in tumor cells is regulated by transcription factors and miRNAs [33][34][35][36][37]. A lncRNA, gastric adenocarcinoma predictive long intergenic noncoding RNA (GAPLINC), also induces CD44 expression by suppressing miR-221, a CD44-targeting miRNA [33].…”
Section: Discussionmentioning
confidence: 99%
“…In HuH7 and mNeat1v1-overexpressing HepG2 cells, the expression of CD44s was observed, while other splicing variants were not detected. It has been reported that CD44 expression in tumor cells is regulated by transcription factors and miRNAs [33][34][35][36][37]. A lncRNA, gastric adenocarcinoma predictive long intergenic noncoding RNA (GAPLINC), also induces CD44 expression by suppressing miR-221, a CD44-targeting miRNA [33].…”
Section: Discussionmentioning
confidence: 99%
“…GLI1 proteins regulate the expression of the pluripotency factors Nanog, octamer binding transcription factor 4 (OCT4), SOX2, WNT-2, CD44, and Kruppel-like factor 4 (KLF4) [148,165,167,168]. Recently, we have shown the novel tGLI1 isoform to promote the glioma stem cell population via upregulation of CD44 and the breast cancer stem cell population through upregulation of CD44, Nanog, OCT4, and Sox2 (Section 6) [31,33]. These data demonstrate that amplified SHH signaling is important for the self-renewal and maintenance of CSCs.…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…Indeed, tGLI1 sustains GBM angiogenesis and growth by promoting the expression of VEGFA and VEGF receptor 2 (VEGFR2) in both GBM and MB [79] (Table 2). Furthermore, tGLI1 is predominantly activated in the highly aggressive mesenchymal subtype of GBM and in GSCs, suggesting its contribution to the acquisition of a more malignant GBM phenotype [83].…”
Section: Tumor Microenvironmentmentioning
confidence: 99%